Animal and Birds Imagery in Poetry and the Qur’ān: A Semantic Study - Khan, Lubna Farah; Rahimullah (Journal of Islamic and Religious Studies, 2021)
Islam looks at the animal world in a realistic way based on its importance in life and benefit to the human being, the Islamic tradition has always held animals in high esteem,” deserving the same level of consideration as humans. The Qur'an opines that “And there is no animal on the earth and no bird that flies with its two wings except for nations like you”. Therefore, we saw animal used in many areas of Islamic thought and legislation the greatest evidence for this is several surahs in the Qur’an, Allah used the titles for them names of the animal e.g. “Surah Al-Baqarah, Surah Al-Anam, Surah Al-Nahl, Surah An-Naml, Surah Al-Anqabut, Surah Al-Fil”. It honors the animal, indicating its position and determining its role in the human life. The Qur'an uses each word for its own connotation and its moral function. The paper has discussed role of animals in humans life, Did they use the apparent meaning referred to by the word or did they use elements that are not of the same type of linguistic units? Birds and animals mentioned in the Quran is an important subject which plays a major role in developing of Human thinking. These names mentioned in several verses for different purpose and action. The reason of mentioning them in Quran is a miracle of Allah. The paper presents the prevalent view of man's superiority over animals and suggests new ways of interpreting the Qur'an.